SAP HANA Cookbook. - Mankala, Chandrasekhar (Packt Publishing, 2013)
An easy-to-understand guide, covering topics using practical scenarios and live examples, and answering all possible questions. If you are a solution architect, developer, modeler, sales leader, business transformation managers, directors, COO, or CIO; this book is perfect for you. If you are interested in other technologies and want to jump-start into SAP, this book gives you the chance to learn SAP HANA. Basic knowledge of RDBMS concepts enough is to get you started.